Can marketing resources contribute to company performance? - Milfelner, Borut (Organizacija (Kranj), 2008)
The study investigates the relationships between market orientation, innovation resources, reputational resources, customer related capabilities, and distribution based assets, as well as their impact on market and financial performance. The results indicate that market orientation is indirectly related to a company's market and financial performance through other four marketing resources. Reputational resources have a positive impact on loyalty, market share, and sales volume, while the impact of innovation resources on market share and sales volume is rather indirect through customer loyalty. While the customer related capabilities significantly impact customer loyalty their impact on market share and sales volume can not be confirmed. On the other side the distribution based assets are weakly related to loyalty and market share and sales volume. General findings indicate that selected marketing resources impact financial performance indirectly through the creation of customer loyalty and directly through market share and sales volume.
Keywords: marketing; podjetja; trženje; tržni odnosi; inovacije; uspešnost poslovanja